The Relationship Between Nutritional Status of Pregnant Women and Newborn Weight in Tio Siringo Ringo Clinic - Pemiliana, Putri Diah; Junia, Nice (Pena Cendekia Insani, 2023)
Background; A healthy pregnancy and a safe physical condition as well as a satisfying emotional state for both mother and fetus. Nutritional problems are an indirect cause of maternal and child deaths which are actually preventable. The low nutritional status of pregnant women during pregnancy can result in some adverse impacts on the mother and baby, including babies born with low birth weight. Objective; the research was to determine the relationship between nutritional status and newborn weight at the Tio Siringo Ringo Clinic. Method; This type of research is an analytic survey using a cross sectional design. The sample of this research was taken the whole population (total sampling) as many as 30 people. Results; cross-tabulation research between pregnant women Lila and baby weight at the Tio Seringgo Ringo Clinic in 2023. That out of 30 respondents (100%). Among them Lila pregnant women who lack chronic energy totaling 3 respondents (10.0%), with LBW 2 respondents (6.7%), and not LBW 1 respondent (3.3). Pregnant women Lila did not lack chronic energy as many as 27 respondents (90.0%), with LBW baby weight as much as 1 respondent (3.3%), and not LBW 26 respondents (86.7%). Conclusion; research there is a relationship Lila Pregnant Women with Baby Weight. With p = 0.001 <0.05 where from 30 respondents. Lila Pregnant women lacked chronic energy as many as 3 respondents (10.0%), Lila Pregnant women did not lack energy as many as 27 respondents (90.0%). It is recommended for pregnant women to increase their knowledge about nutrition fulfillment during pregnancy.